Gamification for Teaching Integrated Circuit Processing in an Introductory VLSI Design Course - Ángel Diéguez; Joan Canals; Sergio Moreno; Anna Vilà (MDPI AG, 2024)
Gamification is being incorporated into university classrooms due to its educational benefits for students learning, including encouraging student behavior and engagement, and consequently improving learning outcomes. Despite gamification being increasingly used in education, little has been developed related to Very-Large-Scale Integration (VLSI). In this article, we describe two different gamification experiences applied to integrated circuit processing and design in an introductory VLSI design course for Electronic Engineers. While gamification in universities is still not very mature and our experience spans only two academic years, we observed that, with the practice of gamifying part of our course, the topics treated in games were profoundly learned and the experience was very positive in every aspect of the teaching-learning process.